Attitude of Students Majoring in Occupational Health and Safety Engineering Towards the Field of Study and Future Career at Ilam University of Medical Sciences - Maryam Hashemi; Shiva Soury; Abdul Hossein Pournajaf (Muhandisī-i bihdāsht-i ḥirfah/ī)
Background and Objective: One of the important factors contributing to students' success is a positive attitude towards their field of study and future careers. Occupational health and safety engineering is a science that works in the field of employee health and work environment safety. Therefore, it is of utmost importance to obtain a thorough understanding of the factors affecting the attitude of students majoring in occupational health and safety engineering. Materials and Methods: In this study, 62 students of occupational health engineering at Ilam University of Medical Sciences were examined in the academic year 2020-2021. The data were collected using the questionnaire of the University of Minnesota, containing 17 items which are rated based on a Likert scale. The data were analyzed using SPSS software. Results: From 66 questionnaires, the mean scores of attitude towards the field of study and future career were calculated at 28.97±4.25 and 24.8±4.7. Considering 22 and 19 as the mean score of the attitude toward the field of study and future career, the scores obtained are more than the acceptable score. Conclusion: The findings of the present study demonstrated a positive attitude towards the field of study and future career. Building the capacity of students to meet the needs of the labor market, familiarizing students with university courses before the national entrance exam, providing advice and support to students in justifying the course and work environment, and better communication between industry and university will improve students' attitudes.